Unmanned Ground and Aerial Vehicles (UGVs-UAVs) for Digital Farming (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
New projections of escalating population growth come as the world faces major global challenges such as climate change, environmental degradation, and food insecurity. Digital farming based on sustainable agricultural practices will potentially overcome the above challenges, simultaneously increasing crop yield while reducing the inputs of farming. In the last decade, unmanned ground and aerial vehicles (UGVs-UAVs) have become a significant tool in digital farming, providing real-time precisely located and scalable data. This Topic provides an overview of the latest applications derived from the use of unmanned ground and aerial vehicles (UGVs-UAVs) within the digital farming framework, including the integration of precision crop management systems and smart operations, and highlights the challenges that remain. Submissions that present novel improvements in both methodologies providing advanced data and analytic algorithms and techniques that accomplish management operations in an autonomous manner are included.